(untitled) (The Insight, 2023)
Introduction: Since the declaration of COVID-19 as a global pandemic, several studies have been conducted to examine associated factors. Limited studies have focused on pregnant women infected with COVID-19 in Bangladesh. Pregnant women may be susceptible to coronavirus infection because of physiological changes in the circulatory and immunological parameters. Aim of the study: This study aimed to evaluate the demographic and clinical profile of Covid-19 positive pregnant women. Methods and materials: This was a cross-sectional study that was conducted in the department of Obstetrics & Gynaecology, Mugda Medical College, Dhaka, Bangladesh from 26 March 2021 to 21 July 2022. A total of 94 pregnant women diagnosed as COVID-19 patients by RT-PCR tests were enrolled in this study as the study subjects. A convenient purposive sampling technic was used in sample selection. All data were processed, analyzed and disseminated by using MS Excel and SPSS version 23.0 program as the necessity. Results: In the study, 23% had comorbidities like HTN, DM, CKD, asthma, or CVD. One-third were in their 2nd pregnancy, 30% in their 3rd pregnancy, and 45% were nulliparous. COVID-19 symptoms included fever (96%) and cough (91%). Abnormal levels of hemoglobin (13%), FBS (40%), WBC (45%), neutrophil count (94%), lymphocyte count (89%), and platelet count (9%) were observed. Conclusion: COVID-19 infection rates appear higher among pregnant women in their 2nd and 3rd pregnancies. The most common symptoms for pregnant COVID-19 cases are fever and cough, while lower abdominal pain is a prevalent pregnancy symptom in these patients.